Efficacy of Revolution® Plus (selamectin plus sarolaner) against Amblyomma americanum (lone star ticks) in cats - Susan Holzmer; Adriano F. Vatta; Sara Chapin; Vickie King; Jamie A. E. Myers (Parasites & Vectors)
Abstract Background The efficacy of a topical combination product, Revolution® Plus, containing selamectin and sarolaner was evaluated for efficacy against Amblyomma americanum ticks in cats. Methods Four laboratory dose confirmation efficacy studies were conducted in different geographical regions of the USA using three distinct US isolates of A. americanum. In each study, ten domestic short-hair cats were randomly allocated to each treatment group based on pretreatment host-suitability tick counts. Cats were infested with approximately 50 unfed adult ticks on day −2. On day 0, cats received either a topical placebo or a single topical dose of Revolution® Plus at the minimum dosage of 6.0 mg/kg selamectin + 1.0 mg/kg sarolaner. Cats were re-infested with approximately 50 unfed adult ticks each on days 5, 12, 19, 26, and 33. Tick counts (comprising live attached and live free ticks) were conducted at 72 h post-treatment and after each subsequent weekly re-infestation. Results No treatment-related adverse reactions occurred in any study. In all studies, placebo-treated cats maintained adequate infestations for the entire study duration, and cats treated with Revolution® Plus had significantly lower (P < 0.0001) least squares mean live (attached and free) tick counts than placebo-treated cats at all time points for at least 1 month. Revolution® Plus provided a mean of > 90% effectiveness based on least squares means 72 h after treatment of existing infestations, and maintained > 99.1% effectiveness 72 h after re-infestation through at least day 29. Conclusions A single dose of Revolution® Plus administered topically at the minimum label dose of 6.0 mg/kg selamectin + 1.0 mg/kg sarolaner provided treatment and control of A. americanum on cats for at least 1 month.